Age‐associated changes in gene expression and developmental competence of bovine oocytes, and a possible countermeasure against age‐associated events. Issue 7 (31st May 2013) - Takeo, S.; Kawahara‐Miki, R.; Goto, H.; Cao, F.; Kimura, K.; Monji, Y.; Kuwayama, T.; Iwata, H.
SUMMARY In general, maternal age affects the quality of oocytes and embryos. The present study aimed to examine the features and age‐associated gene expression profiles of bovine oocytes and embryos as well as to discover possible countermeasures against age‐associated events. Comprehensive gene expression assays of germinal vesicle and metaphase II (MII)‐stage oocytes and 8‐ to 16‐cell‐stage embryos were conducted using next‐generation sequencing technology. The gene expression profiles of aged cows showed high expression of genes related to oxidative phosphorylation, eIF4 and p70S6K signaling, and mitochondrial dysfunction in MII‐stage oocytes. Oocytes derived from aged cows, compared with those derived from their younger counterparts, exhibited high levels of abnormal fertilization and blastocysts with low total cell numbers. Levels of reactive oxygen species (ROS) and SIRT1 were higher in in vitro‐matured oocytes derived from aged cows than in those derived from their younger counterparts. Supplementation of maturation medium with N‐acetyl‐cysteine (NAC), but not resveratrol, reduced the levels of ROS in the oocytes derived from cows of both age groups; however, resveratrol, but not NAC, improved the fertilization ratio. Conversely, EX 527, an inhibitor of SIRT1, increased the ratio of abnormal fertilization. In conclusion, gene expression profiles of oocytes and embryos derived from aged cows differ from those of oocytes and embryos derived from young cows; in particular, oocytes derived from aged cows show protein and mitochondrial dysfunction. In addition, activation of SIRT1 in oocytes may be a potential countermeasure against age‐associated events in oocytes derived from aged cows. Mol. Reprod. Dev. 80: 508–521, 2013. © 2013 Wiley Periodicals, Inc.